A modified dielectric rod resonator with a purer mode distribution based on multi‐gap on the substrate. Issue 4 (3rd February 2019) - Long, Jiawei; Li, En; Guo, Gaofeng
Abstract: In this article, a modified dielectric rod resonator with a purer mode distribution has been proposed for the measurement of the dielectric properties of dielectric materials. The resonator is short circuited at both flat ends by two hard copper‐clad dielectric substrates, which replace the commonly used metal conducting plates. Concentric ring gaps are etched out on one side the dielectric substrates as shorting plates to reduce the degenerate TM0np modes while not affecting the dominant TE0np modes as much as possible. Experimental results show that the modified dielectric rod resonator has a better mode distribution in the high frequency band than the conventional resonator, which is very useful for the accurate and broadband measurement of dielectric materials.